Psychological Impact of Social Networking Sites on Indian Adolescents - Gupta, Debajyoti; Ferah Diba Izgi (Universitas Islam Negeri Madura, 2024)
Social media plays an important role in our life. All the youths living in India and different parts of the world are engaged in social media platform they are busy in themselves to meet new people, make new friends and chat with them. It has been seen that not only young people but also old people are also engaged in social media platform. It is true that there are some merits and demerits in everything. Sometimes excessive use to social networking sites can cause a negative psychological impact on the minds of young people. This research paper will focus on the positive use of social networking sites, effect on the mind on the adolescents due to the excessive use of social networking sites and to suggest some solution to it. Social media has also caused some prominent changes in the attitudes and lifestyles of the adolescents.